Associations of FASN gene polymorphisms with economical traits in Nellore cattle (Bos primigenius indicus) - Pablos de Souza, Fabio Ricardo [UNESP]; Chiquitelli, Milena Gandin [UNESP]; Simielli da Fonseca, Larissa Fernanda [UNESP]; Cardoso, Diercles Franscisco [UNESP]; da Silva Fonseca, Patricia Dias [UNESP]; Ferreira de Camargo, Gregorio Miguel [UNESP]; Monsalves Gil, Fernanda Maria [UNESP]; Boligon, Arione Augusti [UNESP]; Tonhati, Humberto [UNESP]; Zerlotti Mercadante, Maria Eugenia; Albuquerque, Lucia Galvão de [UNESP] (Springer, 2012)
The aim of this study was to identify molecular markers to be applied to marker-assisted selection. Three SNPs of the FASN gene were studied. PCR-RFLP was used for genotyping. The SNPs g.17924A > G, g.17860C > T and g.15603A > G all in the FASN gene were genotyped using the enzymes MscI, DdeI and Hae III, respectively. The animals were raised in extensive systems and belong to three lines selected for growth as part of the Selection Program of Zebu and Caracu Breeds, So Paulo, Brazil. Allele and genotype frequencies were compared between selection lines using the Genepop 3.4. Associations between polymorphisms and the traits studied were evaluated using the PROC MIXED procedure of the SAS/STAT 9.1.3. The G and C alleles were the most frequent alleles of the g.15603A > G and g.17860C > T loci, respectively. The g.17924A > G locus showed no polymorphism in the population studied. Allele and genotype frequencies differed significantly between the NeT line and the NeC and NeS lines. The g.15603A > G polymorphism tended to exert an additive effect on rump fat thickness and male yearling height. For g.17860C > T, an additive effect on male yearling height was observed. Genotype combination analysis revealed a significant effect on loin eye area. Although this study provided evidence of an association between the FASN gene and some traits, more detailed analyses are needed to obtain more efficient molecular markers.
Keywords: Beef cattle; Molecular markers; Marker assisted selection; Carcass traits; growth traits